2013
DOI: 10.9790/2380-0440109
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility status in relation to fallow cycles and landuse practices in shifting cultivated areas of Chandel district Manipur, India.

Abstract: : Shifting cultivation is the major cultivation in hilly region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…pH was found to be lower at FRS compared to SCS in all the seasons (Figure 1). One factor for the increased pH at SCS might be the practise of burning of soils, which supplies ashes to the soil and subsequently raised pH at SCS (Devi & Choudhury, 2013). A positive correlation of pH was observed with soil moisture in both the sites (Table 3 and Table 4).…”
Section: Soil Physico-chemical Parameters At Frs and Scsmentioning
confidence: 91%
See 3 more Smart Citations
“…pH was found to be lower at FRS compared to SCS in all the seasons (Figure 1). One factor for the increased pH at SCS might be the practise of burning of soils, which supplies ashes to the soil and subsequently raised pH at SCS (Devi & Choudhury, 2013). A positive correlation of pH was observed with soil moisture in both the sites (Table 3 and Table 4).…”
Section: Soil Physico-chemical Parameters At Frs and Scsmentioning
confidence: 91%
“…Several workers have reported that soil moisture increased in agricultural systems that employ fallow (Jones & Popham, 1997;Nielsen et al, 2002). The presence of higher soil moisture at FRS may be attributed to higher water retention and surface water entry in the soil due to the presence of denser vegetation (Devi & Choudhury, 2013). Among soil properties, temperature is considered as the most important factor when it comes to mineralization process of organic matter (Arevalo et al, 2012).…”
Section: Soil Physico-chemical Parameters At Frs and Scsmentioning
confidence: 99%
See 2 more Smart Citations
“…In NER, though total area under Shifting Cultivation has been decreasing, yet, the major concern is the shrinking of fallow periods from the earlier practice of 10-15 years to the present one of 2-3 years. Population pressure, limited land resources owing to difficult and inaccessible hilly terrain features, socio-economic impediments, land tenure systems, rapid decline in soil health and predominance of several other anthropogenic degradation over aggradation processes are responsible for this shrink in fallow periods in NER of India" [8]. The shifting cultivation became unsustainable today primarily due to the increase in population that led to increase in food demand.…”
Section: Introductionmentioning
confidence: 99%